HUBUNGAN LITERASI DIGITAL DAN MINAT BACA DENGAN KEMAMPUAN MENULIS AKADEMIK MAHASISWA - Akmal Hamsa; Abdul Haliq; Asis Nojeng (Wahana Literasi: Journal of Language, Literature, and Linguistics, 2025)
This study analyzed the relationship between digital literacy, reading interest, and academic writing skills among students of Indonesian Language and Literature Education. A quantitative approach with a correlational design was employed. The research subjects consisted of 120 students selected through purposive sampling. The research instruments included a digital literacy questionnaire, a reading interest questionnaire, and an academic writing test. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings revealed three main results. First, digital literacy had a positive and significant effect on academic writing skills (original sample = 0.452; t-statistic = 5.723; p < 0.05). Second, reading interest had a positive and significant effect on academic writing skills (original sample = 0.387; t-statistic = 4.891; p < 0.05). Third, digital literacy and reading interest simultaneously explained 56.3% of the variance in academic writing skills (R-square = 0.563). This study concludes that strengthening digital literacy and reading interest plays a crucial role in enhancing students' academic writing quality in the digital era.